Third boundary-value problem for a third-order differential equation with multiple characteristics - Apakov, Yu. P. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We prove the unique solvability of the third boundary-value problem for a third-order differential equation with multiple characteristics containing the second time derivative in a rectangular domain.